Assessing the impact of national anti-HIV sexual health campaigns: trends in the transmission of HIV and other sexually transmitted infections in England. Issue 4 (1st August 2001) - Nicoll, Angus; Hughes, Gwenda; Donnelly, Mary; Livingstone, Shona; De Angelis, Daniela; Fenton, Kevin; Evans, Barry; Gill, O Noël; Catchpole, Mike
Abstract : Objective: To assess the impact of the sexual component of AIDS and HIV campaigns on transmission of HIV and other sexually transmitted infections (STIs). Design: Comparison of time series data. Setting: England, 1971–1999. Outcome measures: HIV transmission and diagnoses among men who have sex with men (MSMs), rates of attendances and specific STI diagnoses (per 100 000 total population) at genitourinary medicine (GUM) clinics. Results: Awareness of AIDS and campaigns in 1983–4 among homosexual men coincided with substantial declines in transmission of HIV and diagnoses of syphilis among MSMs. During general population campaigns in 1986-7 new GUM clinic attendances requiring treatment fell by 117/10 5 in men and 42/10 5 in women. Rates for gonorrhoea fell by 81/10 5 and 43/10 5 and genital herpes by 6/10 5 and 4/10 5, respectively. Previous rises in genital wart rates were interrupted, while rates of attendances not requiring treatment (the "worried well") increased by 47/10 5 and 58/10 5 for men and women, respectively. Since 1987 diagnoses of HIV among MSMs have not declined, averaging 1300–1400 annually. Following a period of unchanging rates there have been substantial increases in GUM attendances requiring treatment, notably for gonorrhoea, syphilis, and viral STIs since 1995. Conclusions: Self help initiatives and awareness among homosexual men in 1983–4 contributed significantly to a fall in HIV transmission among MSMs, and the general campaigns of 1986–7 were associated with similar effects on all STI transmission. Both effects seem to have occurred through changing sexual behaviour, and probably contributed to the UK's low national HIV prevalence. Bacterial STI incidence has increased significantly since 1995 and there is no evidence that recent prevention initiatives have reduced HIV transmission among MSMs, hence sexual health initiatives need to be comprehensively reinvigorated in England.